Comparative phylogeography reveals a shared impact of pleistocene environmental change in shaping genetic diversity within nine Anopheles mosquito species across the Indo-Burma biodiversity hotspot - Morgan, K.; O'Loughlin, S.M.; Chen, B.; Linton, Y.M.; Thongwat, D.; Somboon, P.; Fong, Mun Yik; Butlin, R.; Verity, R.; Prakash, A.; Htun, P.T.; Hlaing, T.; et al. (Blackwell Publishing, 2011)
South-East Asia is one of the world's richest regions in terms of biodiversity. An understanding of the distribution of diversity and the factors shaping it is lacking, yet essential for identifying conservation priorities for the region's highly threatened biodiversity. Here, we take a large-scale comparative approach, combining data from nine forest-associated Anopheles mosquito species and using statistical phylogeographical methods to disentangle the effects of environmental history, species-specific ecology and random coalescent effects. Spatially explicit modelling of Pleistocene demographic history supports a common influence of environmental events in shaping the genetic diversity of all species examined, despite differences in species' mtDNA gene trees. Populations were periodically restricted to allopatric northeastern and northwestern refugia, most likely due to Pleistocene forest fragmentation. Subsequent southwards post-glacial recolonization is supported by a north-south gradient of decreasing genetic diversity. Repeated allopatric fragmentation and recolonization have led to the formation of deeply divergent geographical lineages within four species and a suture zone where these intraspecific lineages meet along the Thai-Myanmar border. A common environmental influence for this divergence was further indicated by strong support for simultaneous divergence within the same four species, dating to approximately 900 thousand years ago (kya). Differences in the geographical structuring of genetic diversity between species are probably the result of varying species' biology. The findings have important implications for conservation planning; if the refugial regions and suture zone identified here are shared by other forest taxa, the unique and high levels of genetic diversity they house will make these areas conservation priorities.